STD rapid assessment in Rwandan refugee camps in Tanzania. Issue 1 (February 1997) - Mayaud, P; Msuya, W; Todd, J; Kaatano, G; West, B; Begkoyian, G; Grosskurth, H; Mabey, D
Abstract : OBJECTIVE: To obtain baseline information on sexually transmitted diseases (STDs) in the Rwandan refugees camps in Tanzania, prior to establishment of STD services. SETTING: The largest camps of Rwandan refugees in the Ngara District of Tanzania (estimated population 300, 000). The study was carried out in 8 days in August 1994. SUBJECTS AND METHODS: A rapid assessment technique was used to measure STD prevalences among: (i) 100 antenatal clinic attenders (ANC); (ii) 239 men from outpatient clinics (OPD); and (iii) 289 men from the community. Interviews (by questionnaire) and genital examination were performed for all participants; sampling for females included genital swabs for the the diagnosis of Neisseria gonorrhoeae (NG), Candida albicans (CA), Trichomonas vaginalis (TV), bacterial vaginosis (BV) and a blood sample for syphilis serology. Men provided urine samples which were screened for leucocytes using the leucocyte esterase (LE) dipstick; urethral swabs for Gram stain were taken from men with a reactive LE test and from those with symptoms or signs of urethritis. OPD males provided a blood sample for syphilis serology. RESULTS: All groups reported frequent experience with STDs and engaging in risky sexual behaviour prior to the survey. During the establishment of the camps, sexual activity was reportedly low. Over 50% of ANC attenders were infected with agents causing vaginitis (TV/BV/CA) and 3% were infected with NG. The prevalence of active syphilis was 4%. In the male outpatients, the prevalence of urethritis was 2.6% and of serological syphilis was 6.1%. Among males in the community, the prevalence of urethritis was 2.9% (the majority being asymptomatic infections). We noted frequent over-reporting of STD symptoms, unconfirmed clinically or biologically. CONCLUSIONS: STD case detection and management should be improved by training health workers in using the WHO syndromic approach, and through IEC campaigns encouraging attendance at clinics. Rapid epidemiological methods provide quick and useful information at low cost in refugee camps.